2011
DOI: 10.3171/2010.10.jns1029
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus associated with vestibular schwannomas: management options and factors predicting the outcome

Abstract: Object The current, generally accepted optimal management for hydrocephalus related to vestibular schwannomas (VSs) is primary tumor removal, with further treatment reserved only for patients who remain symptomatic. Previous studies have shown, however, that this management can lead to an increase in surgery-related complications. In this study, the authors evaluated their experience with the treatment of such patients, with the aim of identifying the following: 1) the parameters correlating to the need for sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 30 publications
3
46
0
6
Order By: Relevance
“…As expected, increased tumor size is a risk factor for development of postoperative hydrocephalus. 10 If symptomatic obstructive hydrocephalus is present, we prefer to place an external ventricular drain at the time of craniotomy with the goal of weaning the drain postoperatively, if possible, and shunt placement if necessary. In the particular case described in the accompanying video, due to the patient's gravid state and associated risks, an initial shunting procedure was performed to temporize the patient's symptoms until postpartum to allow for delayed tumor resection.…”
Section: 2530mentioning
confidence: 99%
“…As expected, increased tumor size is a risk factor for development of postoperative hydrocephalus. 10 If symptomatic obstructive hydrocephalus is present, we prefer to place an external ventricular drain at the time of craniotomy with the goal of weaning the drain postoperatively, if possible, and shunt placement if necessary. In the particular case described in the accompanying video, due to the patient's gravid state and associated risks, an initial shunting procedure was performed to temporize the patient's symptoms until postpartum to allow for delayed tumor resection.…”
Section: 2530mentioning
confidence: 99%
“…The incidence of preoperative shunting was as high as 66% in the series reported by Ramamurthy. 4 Gerganov VM et al 10 recommended placement of external ventricular drainage (EVD) or VP shunt prior to surgery as surgery in patients with hydrocephalus and increased ICP is presumably more challenging, and related to worse outcome or higher complication rates. They found that the general and functional outcome in patients with primary VS removal is independent of the presence of hydrocephalus.…”
Section: Preoperative Signs and Symptomsmentioning
confidence: 99%
“…The presence of schwannoma outside the blood-brain barrier allows blood proteins to pass through the cleft and interendothelial junctions of the tumor to the surrounding CSF [12]. Communicating hydrocephalus is thought to be predominant in older SV carriers [10] [16]. We will simply say that the presence of the neuroma is a predisposing factor to hydrocephalus whatever the age.…”
Section: Hydrocephalusmentioning
confidence: 99%